2003
DOI: 10.1186/1471-2458-3-35
|View full text |Cite
|
Sign up to set email alerts
|

A study on cercarial dermatitis in Khuzestan province, south western Iran

Abstract: Background: Cercarial dermatitis' or swimmer's itch' is an itchy inflammatory response to the penetration of the skin by non-human schistosome parasites. In the hot season, (May to September) in Khuzestan province in the south west of Iran, swimming in canals and agriculture activities in swampy areas are common. This survey was made on people from villages north of Ahwaz city in south west Iran, to estimate cercarial dermatitis in this region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 10 publications
(4 reference statements)
2
26
1
1
Order By: Relevance
“…In addition, many young chilt t dren work on the agricultural farms without any protection on their hands or feet where S. haematob b bium as well as animal schistosome cercariae can readily penetrate the skin. 8 Lack of S. haematobium cert t cariae in our samples in this region revealed that snails are free from this parasite and support the theory that transmission of schistosomes cecart t ia does not occur in the districts and therefore this disease is still under control, which is good news for int t habitants of the region as well as for local health authorities. Because of the presence of Bulinus in the other parts of province, use of this protot t col for evaluating the transmission status of S. haematobium by finding cercariae of the parasite among local B. truncatus is recommended.…”
Section: The Use Of Cercariae Infect T Tion Of the Bulinus Truncat T supporting
confidence: 78%
“…In addition, many young chilt t dren work on the agricultural farms without any protection on their hands or feet where S. haematob b bium as well as animal schistosome cercariae can readily penetrate the skin. 8 Lack of S. haematobium cert t cariae in our samples in this region revealed that snails are free from this parasite and support the theory that transmission of schistosomes cecart t ia does not occur in the districts and therefore this disease is still under control, which is good news for int t habitants of the region as well as for local health authorities. Because of the presence of Bulinus in the other parts of province, use of this protot t col for evaluating the transmission status of S. haematobium by finding cercariae of the parasite among local B. truncatus is recommended.…”
Section: The Use Of Cercariae Infect T Tion Of the Bulinus Truncat T supporting
confidence: 78%
“…Cercarial dermatitis has been recorded in Canada, 11.8%, US, 17.3% and Chile,3% [12] . In the present study, 6.1% of the population were infected but in Dr. Farahnak et al's study for investigating the prevalence of cercarial dermatitis in Khuzestan province (among the inhabitants of the north of Ahvaz), 1.1% of the population was infected [7] . Because of rainfall, high humidity and bird's winter migratory in this province, we have more infected people.…”
Section: Discussioncontrasting
confidence: 64%
“…Thus the migratory birds, contaminate the snails by contaminating the water and Egg excretion, and these snails cercaria excreted in the water and infect the people who are somehow in contact with fresh waters. This disease is a kind of Zoonosis diseases and is reported in the north ( Mazandaran and Gilan province) and south( Khuzestan province) of the country [6,7] . Cecarial dermatitis, is regarded a new disease in Europe [8,9] .…”
Section: Introductionmentioning
confidence: 99%
“…These outbreaks have been reviewed extensively (7,8,70,71). Species of Trichobilharzia have been reported to cause dermatitis from other areas as well, such as Rwanda-Burundi (72), South Africa (73,74), New Zealand and Australia (75)(76)(77)(78)(79), Malaysia/Indonesia (80)(81)(82), Iran (65,(83)(84)(85)(86), United Arab Emirates (66), Thailand (87), and China (88,89) in the Eastern Hemisphere and Argentina (57,90,91), Chile (11), and El Salvador (92) in the Western Hemisphere. We are just beginning to better understand the significant disease components for dermatitis as a global problem.…”
Section: Diversity Of Schistosomes Causing Dermatitismentioning
confidence: 99%